PENERAPAN GOOD LOGISTIC PRACTICES UNTUK PRODUK PERIKANAN - Winiati Pudji Rahayu; Wibisono Wibisono (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2016)
The utilization of Indonesia’s fisheries potential should be supported by the development of fisheries industry, more specifically by the improvement on fisheries supply chain management. It is needed to preserve the quality and safety of fisheries product from sea to consumers’ table and the sustainable fisheries supply. The fisheries product is perishable therefore the appropriate handling and full controlled process are needed to maintain product quality and safety. In fisheries industry, quality and safety can be maintained by applying good logistic practices (GLoP). GLoP is best practices ofcold chain management supported by quality and safety control system such as good manufacturing practices (GMP), standard sanitation operating procedure (SSOP) and hazard analysis critical control point (HACCP). On the other hand, the sustainability of fisheries supply canbe achieved by applying full controlled resources management. The commitment and cooperation of all parties on fisheries industry, as well as the standard implementation of fishery management is needed to improve quality and quantity of Indonesia’s fisheries products.